A novel method for testing automatic systems for controlling the spray boom height. (October 2018) - Herbst, Andreas; Osteroth, Hans-Jürgen; Stendel, Hartje
Abstract : Automatic boom height control (BHC) systems for sprayers have become more common in recent years. The accuracy of the BHC is dependent on the quality of the height measurement as well as on the control algorithm that should be tailored to the dynamic behaviour of the spray boom and its suspension. There is a need for evaluating BHC performance but there is no objective test method available. A protocol was developed for assessing the control accuracy of BHC systems based on a stationary test bench consisting of target area units placed below the height sensors of the sprayer simulating a ground or canopy surface profile. This study should prove the suitability of this test method, of the target area profiles used and of different statistical parameters describing the test results. The test bench and the protocol developed have proved appropriate for evaluating the performance of BHC systems in a stationary test under defined conditions. Test replications gave consistent results. Several statistical parameters were found suitable to characterise the BHC performance but the standard deviation from set point provided the best selectivity. A smooth and a rough field profile were used for the test in comparison to a synthetic profile consisting of different low frequency harmonics. The rough field and the synthetic profile gave similar results. Opposite to the smooth field, tests using these profiles appear sufficiently selective. It turned out that in some cases the profiles could alter comparative test results. This needs further examination. The test bench developed for this study can be considered a potential basis of a standardised protocol for BHC assessment as well as for the definition of performance limits. Highlights: Novel test protocol for sprayer boom height control systems based on a test bench. The test procedure allows to simulate arbitrary target area profiles. The protocol proved appropriate to evaluate boom height control systems. The method is a potential basis for an international test standard.